EEG in motion: Using an oddball task to explore motor interference in active skateboarding. (15th March 2021) - Robles, Daniel; Kuziek, Jonathan W. P.; Wlasitz, Nicole A.; Bartlett, Nathan T.; Hurd, Pete L.; Mathewson, Kyle E.
Abstract: Recent advancements in portable computer devices have opened new avenues in the study of human cognition outside research laboratories. This flexibility in methodology has led to the publication of several electroencephalography studies recording brain responses in real‐world scenarios such as cycling and walking outside. In the present study, we tested the classic auditory oddball task while participants moved around an indoor running track using an electric skateboard. This novel approach allows for the study of attention in motion while virtually removing body movement. Using the skateboard auditory oddball paradigm, we found reliable and expected standard–target differences in the P3 and MMN/N2b event‐related potentials. We also recorded baseline electroencephalography activity and found that, compared to this baseline, alpha power is attenuated in frontal and parietal regions during skateboarding. In order to explore the influence of motor interference in cognitive resources during skateboarding, we compared participants' preferred riding stance (baseline level of riding difficulty) versus their non‐preferred stance (increased level of riding difficulty). We found that an increase in riding difficulty did not modulate the P3 and tonic alpha amplitude during skateboard motion. These results suggest that increases in motor demands might not lead to reductions in cognitive resources as shown in previous literature. Abstract : Brain activity was recorded while participants simultaneously rode a self‐propelling skateboard around a busy running track and completed a classic auditory oddball task. We found expected and reliable differences between target and standard tones in the P3 and MMN/N2b components. We found that increases in motor load did not significantly modulate the P3 and MMN/N2b in the cognitive task as previously shown in dual‐task studies.